Escarabajos coprófagos de un escenario ganadero tipico de la región de los Tuxtlas, Veracruz, México: importancia del paisaje en la composición de un gremio funcional - Montes De Oca, Enrique (Instituto de Ecología, A.C., 2001)
A guild of nine crepuscular/nocturnal dung beetle species associated to a typical cattle ranching environment of the tropical regions was studied. The influence of some of the landscape elements and its conformation on the abundance and distribution of these species was analyzed. The defined guild plays an ecological role in this environment promoted by the cattle ranching activities and the dung supply. The maintenance and coexistence of the non dominant with the dominant species are facilitated by the structure and cover quality of the landscape elements and their spatial conformation. Landscape processes are important for Onthophagus batesi before the probable competitive action exerted by open-area species such as Digitonthophagus gazella and species adapted to more shady places like Ateuchus illaesum and Copris laeviceps. Enrichment of the guild by mean of a suitable conformation of the landscape could help to improve the functional role of the dung beetles contributing to the sustainability of cattle management in Los Tuxtlas.